INFORMATION PROCESSING, KNOWLEDGE DEVELOPMENT, AND STRATEGIC SUPPLY CHAIN PERFORMANCE. - Hult, G. T. M.; Ketchen, D. J.; Slater, S. F. (Academy of Management Journal, 2004)
Little is known about why some supply chains perform well while others do not. Drawing on the knowledge-based view of the firm and theory from the information processing and organizational learning...